Fake News and Political Misinformation: Implications for Democratic Process in Nigeria - John Adegoke Akinola; Adeyinka Patrick Adewumi; Tahir Adekunle Ijaiya (Covenant University Journal of Politics and International Affairs, 2024)
The media space in Nigeria has morphed over the years from traditional to digital outlets, with social media as a critical instrument in information dissemination. The transition has revolutionised and democratised the distribution and consumption of information. However, this has also created opportunities for fast and widespread fake news (misinformation and disinformation). Given this, this study examines the implications of political misinformation for the democratic process in Nigeria. Using a qualitative approach based on secondary sources and content and thematic analysis, this study discovers that the unregulated nature of new media, with the proliferation of fake news, consequently impacts voter attitudes, electoral outcomes, public trust, and social cohesion, all of which bears consequences on the country’s democratic process. It further highlights the government’s endeavours to regulate social media to contain the dissemination of news that threatens the political, economic and social foundations of the Nigerian state. It proposes recommendations, including strengthening media literacy, collaborative fact-checking, promoting social media platform responsibility, revising the legal framework, international collaboration, encouraging responsible online behaviour, and launching public awareness campaigns. These recommendations collectively aim to safeguard Nigeria’s democratic integrity, uphold public opinion, and fortify the credibility of its institutions within the digital age’s interconnected world.